Effects of cracked corn on growth performance and stomach lesions in finishing pigs - S M Williams; C B Paulk; S Issa; Terry L Gugle; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 208 pigs (104 barrows and 104 gilts, initial average 138 lb) were used in a 63-d experiment to determine the effects of adding cracked corn to diets for finishing pigs. The pigs were sorted by ancestry and blocked by weight with 13 pigs per pen and 4 pens per treatment. Treatments were corn-soybean meal-based with none, 10, 20, or 40% roller-milled corn (mean particle size of 3,549 Î¼m). Particle size for the none, 10, 20, and 40% cracked corn diets were 684, 926, 979, and 1,187 Î¼m, respectively. Feed and water were offered ad libitum until slaughter (average final BW of 268 lb) at a commercial facility. Overall (d 0 to 63), increasing cracked corn from none to 40% had no effect on ADG (P>0.98) and ADFI (P>0.41), but F/G was numerically poorer (linear, P<0.11). Adding cracked corn had no effect on HCW (P>0.17) or backfat thickness (P>0.69), but dressing percentage was decreased (linear effect, P<0.05). For both stomach keratinization and ulcer scores, as the percentage of cracked corn increased, there was a decrease (linear, P<0.009) in scores for ulcers and stomach keratinization (scale of 0 = none, 1 = mild, 2 = moderate, and 3 = severe), but even the worst treatment had an average lesion score of less than mild. Our results indicate that increasing cracked corn from none to 40% of diets for finishing pigs did not affect rate of gain but worsened F/G and dressing percentage with only slight improvements in scores for stomach lesions.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Cracked corn; Finishing pigs; Stomach ulcers